dSpaced-based finite-set model predictive control for half-bridge bidirectional dc-dc converter in hybrid energy storage system - Xu, Rui (2017)
This report presents a model predictive control (MPC) method for the bidirectional DC-DC converter and two practicable MPC algorithms are proposed. Before employing any control method, strategies concerning designing bidirectional DC-DC converters are discussed. A traditional control scheme, like Proportional-Integral-Derivative (PID) control, is applied to the bidirectional DC-DC converters and the methodology of tuning three PID parameters is discussed as well. Then, MPC algorithms aiming at controlling bidirectional DC-DC converters to a desirable performance were compiled through MATLAB Simulink. The feasibility and functionality of the MPC method are assessed via simulation and hardware based on the compiled MATLAB codes. Eventually, considering four demands that bidirectional DC-DC converters are expected to meet, namely fast response speed, short settling time, tiny steady state error and small overshoot, the performance of the PID control and that of MPC were compared both in simulation and hardware in order to obtain a dependable suggestion for future work. An ultimate conclusion regarding the merits and drawbacks of each control method is drawn too.